2021
DOI: 10.7554/elife.64846
|View full text |Cite
|
Sign up to set email alerts
|

NF1 regulates mesenchymal glioblastoma plasticity and aggressiveness through the AP-1 transcription factor FOSL1

Abstract: The molecular basis underlying glioblastoma (GBM) heterogeneity and plasticity is not fully understood. Using transcriptomic data of human patient-derived brain tumor stem cell lines (BTSCs), classified based on GBM-intrinsic signatures, we identify the AP-1 transcription factor FOSL1 as a key regulator of the mesenchymal (MES) subtype. We provide a mechanistic basis to the role of the neurofibromatosis type 1 gene (NF1), a negative regulator of the RAS/MAPK pathway, in GBM mesenchymal transformation through t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 97 publications
7
54
0
Order By: Relevance
“…To narrow down the number of “candidate” DEGs and determine potential “key” genes for HCC development [ 30 , 31 , 33 , 34 ], a PPI network of 145 DEGs was constructed to visualize the relationships between genes, followed by functional analysis. Based on their connectivity level, the top ten hub genes identified included CCNB1, MAD2L1, CCNA2, AURKA, ZWINT, HMMR, TPX2, EZH2, and OIP5.…”
Section: Discussionmentioning
confidence: 99%
“…To narrow down the number of “candidate” DEGs and determine potential “key” genes for HCC development [ 30 , 31 , 33 , 34 ], a PPI network of 145 DEGs was constructed to visualize the relationships between genes, followed by functional analysis. Based on their connectivity level, the top ten hub genes identified included CCNB1, MAD2L1, CCNA2, AURKA, ZWINT, HMMR, TPX2, EZH2, and OIP5.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is accompanied by altering the shape of tumor cells and impairing their anchorage. For instance, FOSL1 accumulation in non-tumorigenic glioma cell lines in vitro confers tumorigenicity [87]. On the contrary, diminishing the FOSL1 level by 80% restores cell morphology, impairs cell motility, and normalizes the metabolic processes [88].…”
Section: Role Of Fosl1 In Tumorigenesis 41 Fosl1 Expression Pattern I...mentioning
confidence: 99%
“…Moreover, immunotherapies seem to be not only a promising strategy for mesenchymal gliomas, but they are also an important treatment option for NF1-related melanomas, lung carcinomas, or MPNST. Recently, loss of NF1 was shown to modulate FOS like 1, AP-1 transcription factor subunit (FOSL1) expression, which is a key regulator for stemness, mesenchymal shift, and plasticity [ 113 ]. Transcription factor FOSL1 is overexpressed in cancer and associated with worse outcomes and EMT as well as with glioma malignancy [ 113 ].…”
Section: Mesenchymal Glioblastomas Accumulate Neurofibromatosis Type 1 (Nf1) Gene Alterationsmentioning
confidence: 99%
“…Recently, loss of NF1 was shown to modulate FOS like 1, AP-1 transcription factor subunit (FOSL1) expression, which is a key regulator for stemness, mesenchymal shift, and plasticity [ 113 ]. Transcription factor FOSL1 is overexpressed in cancer and associated with worse outcomes and EMT as well as with glioma malignancy [ 113 ]. The authors demonstrated that FOSL1 depletion in NF1 mutant human brain tumour stem cells and KRAS mutant mouse neural stem cells resulted in the loss of the MES signature and a reduction in stem cell properties.…”
Section: Mesenchymal Glioblastomas Accumulate Neurofibromatosis Type 1 (Nf1) Gene Alterationsmentioning
confidence: 99%
See 1 more Smart Citation